A Review On India's Rural Development And Agricultural Infrastructure (Journal of Pharmaceutical Negative Results, 2023)
The studies all agree that rural infrastructure is a requirement for dramatically raising human well-being and astonishingly boosting agricultural development. Infrastructure projects, however, demand huge upfront cash commitments, lengthy gestation times, and large incremental cash requirements. High risk, low rate of return on investment, and production ratio. Increased crop yields, which in turn foster agricultural growth, have a clear and significant association with farmers' access to institutional finance and markets. The development of agricultural infrastructure in India has the ability to upgrade the country's current traditional agriculture and subsistence farming practises into the most cutting-edge, lucrative, and dynamic farming systems. Agricultural infrastructures are divided into two categories, according to Wharton (1967)(: I capital intensive, such as irrigation, roads, and bridges [ii] institutional infrastructure, such as formal and informal institutions, and [iii] capital intensive, such as extension services.